ENHANCING GRAPHITIC CARBON CONTENT OF CARBON-BASED ELECTRODE MATERIALS BY PULSED ELECTROPHORETIC DEPOSITION FOR ELECTROCHEMICAL CAPACITOR - Lau, K.T.; Azam, M.A.; Manaf, M.E.A.; Zaimi, M.; Suan, M.S.M.; Yaacob, N.A.; Narayanasamy, J.; Samat, K.F. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Crystallinity of carbon electrode materials and their deposition techniques are the crucial factors for electrochemical capacitor (EC) performance. The present work investigates deposit yield and graphitic content of activated carbon (AC) and CNT coatings deposited by pulsed electrophoretic deposition (EPD). Pulse voltage with pulse separation times of 30 to 50 s, alternated with the long pulse width (i.e. 2.5 min) was applied. Although the pulse separation time at 30 s reduced the CNT coating yield, its graphitic content increased by 40 % as compared to the CNT coating deposited by continuous voltage EPD, as indicated by the IG/ID ratio of Raman spectra. However, graphitic content increase was not observed in the deposition of AC. Consequently, the CNT deposition gained a higher graphitic-nongraphitic content ratio than the AC. This finding opened up the possibility of the EC performance enhancement by the graphitic CNT control in electrode materials through EPD process.